Toxicidade e biorremoção de Manganês pela Cianobactéria Microcystis protocystis - Maria Beatrice Manno Boulanger (2018)
Manganese (Mn) is one of the great highlights of the global iron-alloys industry and its main application is currently in the production of iron and steel. Because it is an essential element, but toxic in high concentrations, many studies have been carried out to know the toxicity and bioaccumulation of this metal in the food chain. This study analyzed the toxicity and bioremediation capacity of Mn by the Microcystis protocystis and the possibility of removal of this metal from contaminated water through processes of bioaccumulation, especially absorption and adsorption. The two hypotheses tested in this study were that i) M. protocystis exhibits different levels of tolerance to Mn as a function of concentration, and ii) this cyanobacteria has the ability to remove Mn from aqueous medium in both conditions: living cells and lyophilized biomass. The EC50 test was performed at concentrations: 0.5; 0.8; 1,3; 2; 3.3; 5.2; 8.4; 13.4; 21.5; 34.4; and 55 mg L-1 Mn. The experiments with lyophilized biomass were carried out with concentrations of 0.5; 1; 5; 10; 15; 25; 50; 75; 100; 125 mg L1and the data were analyzed according to the Langmuir and Freundlich isotherms. The results showed that 34.4 mg L-1 of Mn inhibited the growth of this cyanobacteria by 50%, and being able to remove 9.8% at a concentration of 13.4 mg L-1 of Mn. In the lyophilized biomass, the adsorption equilibrium time stabilized at 4 h with maximum adsorption at pH 4, with a maximum amount of adsorbed metal (qmáx) of 4.319 mg g-1. The results showed that lyophilized M. protocystis is efficient in the removal of Mn from contaminated water at low concentrations, and studies are needed to enhance Mn removal in a commercially viable process